The lost wife - Richman, Alyson (New York : Berkley Books, 2011)
During the last moments of calm in prewar Prague, Lenka, a young art student, and Josef, who is studying medicine, fall in love. With the promise of a better future, they marry--only to have their dreams shattered by the imminent Nazi invasion. Like so many others, they are torn apart by the currents of war.
Includes readers guide.
Keywords: Jews -- Fiction; World War, 1939-1945 -- Fiction; Marriage -- Fiction; Prague (Czech Republic) -- Fiction; Love stories